Differential production of slime under aerobic and anaerobic conditions. - Barker, L P (1990)
A series of 37 clinical isolates of coagulase-negative staphylococci previously identified as negative for slime production by the tube test were reexamined by the tissue culture plate test under aerobic and anaerobic conditions. None of the strains produced slime under anaerobic conditions; however, five strains (13%) produced slime under aerobic conditions.